Research in the application of artificial intelligence to lung cancer diagnosis - Liu, Wenjuan; Shen, Nan; Zhang, Limin; Wang, Xiaoxi; Chen, Bainan; Liu, Zhuo; Yang, Chao (Frontiers in Medicine, 2024)
The morbidity and mortality rates in lung cancer are high worldwide. Early diagnosis and personalized treatment are important to manage this public health issue. In recent years, artificial intelligence (AI) has played increasingly important roles in early screening, auxiliary diagnosis, and prognostic assessment. AI uses algorithms to extract quantitative feature information from high-volume and high-latitude data and learn existing data to predict disease outcomes. In this review, we describe the current uses of AI in lung cancer-focused pathomics, imageomics, and genomics applications.